Reading toward Empathy: Encouraging Student Engagement with Characters from Free-choice Books - LUKAŠ, Mirko; BEGOVIĆ, Ines (Anafora, 2023)
Throughout a person’s life, emphatic engagement is approached from the position of an educational ideal, and is seen as the ability to understand other people’s emotions and to identify with them. Educational programs primarily aimed at promoting the development of humane behavior and empathy are becoming increasingly important in the educational process. Reasons for encouraging the skill of emphatic engagement stem from viewing it as the foundation for a positive development and mental health of children. Earlier research suggests that literature can influence a child’s emphatic engagement if they become emotionally invested in the story, namely, when reading about an individual of the same age and thinking about what they would do in the same situation. This paper points to the possibilities of children’s free choice of school reading assignments under the guidance of teachers with the aim of enriching and developing their emphatic engagement through reading and thinking about the contents of the work. The research analyzes the content of selected literary works for children which are not on the list of compulsory school reading assignments. A randomly selected sample of works includes recommendations for a free choice of readings for the fourth or fifth grade of primary school. Those are: George by Alex Gino, Tuck Everlasting by Natalie Babbitt, Raymie Nightingale by Kate DiCamillo, Wonder and Auggie & Me: Three Wonder Stories by R. J. Palacio, and Bridge to Terabithia by Katherine Paterson. The content analysis of selected works identifies topics and relationships as well as positive and negative behaviors the descriptions of which have the task of encouraging the readers’ emphatic engagement. Such engagement opens up the path to identity formation, friendships and opposition to bullying, acceptance of oneself and others, compassion, and support.